Factors fostering the inclusion of students with disabilities during their academic career at the University Center of Health Sciences of the University of Guadalajara - Elicerio Conchas, David; Hernández Carrillo, Pamela Georgina; Pérez Zúñiga, Ricardo (Frontiers in Education, 2025)
The results of a qualitative study whose objective was to understand, from the experience of 13 students with disabilities of the University Center of Health Sciences, the factors that favor their inclusion and the barriers they have faced during their academic trajectory are presented. The favoring factors and barriers identified for inclusion were analyzed from the ecological theory of human development and the model of inclusive schools. It was observed that they are present in the different subsystems in which students with disabilities develop: personal, family, institutional and contextual, as well as in three moments of their trajectory: access, permanence and graduation. The findings were also grouped into the three dimensions of the inclusion index (inclusive culture, policies and practices) and show that the main factors that favor the inclusion of students with disabilities are: the student’s own knowledge of his or her condition and needs, family support, peer support, help and guidance from different institutional agencies, and financial support. In terms of barriers, it highlights the need to improve institutional and external infrastructure and knowledge about inclusion and people with disabilities.